Global epidemiology of serogroup B meningococcal disease and opportunities for prevention with novel recombinant protein vaccines. Issue 5 (4th May 2018) - Villena, Rodolfo; Safadi, Marco Aurelio P.; Valenzuela, María Teresa; Torres, Juan P.; Finn, Adam; O'Ryan, Miguel
ABSTRACT: Background : Meningococcal disease (MD) is a major cause of meningitis and sepsis worldwide, with a high case fatality rate and frequent sequelae. Neisseria meningitidis serogroups A, B, C, W, X and Y are responsible for most of these life-threatening infections, and its unpredictable epidemiology can cause outbreaks in communities, with significant health, social and economic impact. Currently, serogroup B is the main cause of MD in Europe and North America and one of the most prevalent serogroups in Latin America. Mass vaccination strategies using polysaccharide vaccines have been deployed since the 1970s and the use of conjugate vaccines has controlled endemic and epidemic disease caused by serogroups A, C, W and Y and more recently serogroup B using geographically-specific outer membrane vesicle based vaccines. Two novel protein-based vaccines are a significant addition to our armamentarium against N. meningitidis as they provide broad coverage against highly diverse strains in serogroup B and other groups. Early safety, effectiveness and impact data of these vaccines are encouraging. These novel serogroup B vaccines should be actively considered for individuals at increased risk of disease and to control serogroup B outbreaks occurring in institutions or specific regions, as they are likely to save lives and prevent severe sequelae. Incorporation into national programs will require thorough country-specific analysis.